Digitalizing Faculty Career Advancement: How SIM-PAK Quality Accelerates Academic Rank Promotion - Joko Yoeliyanto; Bambang Yulianto; Syunu Trihantoyo; Dewi Fitrotus Sa’diyah (Business and Applied Management Journal, 2025)
Digital transformation in higher education requires effective academic information systems to support governance and improve teaching quality. One strategic process in faculty resource management is academic rank promotion, which demands a transparent, efficient, and accountable administrative system. This study examines the role of Credit Point Assessment Management Information System (SIM-PAK) implementation quality in shaping faculty satisfaction and enhancing the effectiveness and speed of academic rank promotion processes. A quantitative survey was conducted involving 267 faculty members who have used SIM-PAK. Data were collected through a structured questionnaire measured on a five-point Likert scale and analyzed using Partial Least Squares–Structural Equation Modeling (SEM-PLS). The results show that SIM-PAK implementation quality positively and significantly affects process effectiveness (β = 0.52; p < 0.001), process speed (β = 0.47; p < 0.001), and faculty satisfaction (β = 0.61; p < 0.001). This study highlights system implementation quality as a key factor in reducing administrative workload, enabling faculty to focus more on teaching innovation and learning development. Practically, universities should prioritize high-quality academic information systems to enhance faculty performance and institutional effectiveness.